Domestic Violence Experience in Omaha, Nebraska, 1986-1987 - Dunford, Franklyn W. ([Verlag nicht ermittelbar], 1991)
The purpose of this data collection was to corroborate the findings of SPECIFIC DETERRENT EFFECTS OF ARREST FOR DOMESTIC ASSAULT: MINNEAPOLIS, 1981-1982 (ICPSR 8250) that arrest is an effective deterrent against continued domestic assaults. The data addressed the following questions: (1) To what extent does arrest decrease the likelihood of continued violence, as assessed by the victim? (2) To what extent does arrest decrease the likelihood of continued complaints of crime, as assessed by police records? (3) What are the differences in arrest recidivism between cases that involved arrest versus cases that involved mediation, separation, warrant issued, or no warrant issued? Domestic violence cases in three sectors of Omaha, Nebraska, meeting established eligibility criteria, were assigned to one of five experimental treatments: mediation, separation, arrest, warrant issued, or no warrant issued. Data for victim reports were collected from three interviews with the victims conducted one week, six months, and 12 months after the domestic violence incident. Arrest, charge, and complaint data were collected on the suspects at six- and twelve-month intervals following the original domestic violence incident. The investigators used arrest recidivism, continued complaints of crime, and victim reports of repeated violence (fear of injury, pushing/hitting, and physical injury) as outcome measures to assess the extent to which treatments prevented subsequent conflicts. Other variables include victim's level of fear, self-esteem, locus of control, and welfare dependency, changes in the relationship between suspect and victim, extent of the victim's injury, and extent of drug use by the victim and the suspect. Demographic variables include race, age, sex, income, occupational status, and marital status.